2012
DOI: 10.1007/s00520-012-1572-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of modified early-goal directed therapy for sepsis in the emergency center of a comprehensive cancer center

Abstract: Implementation of a standardized sepsis order set and algorithm to improve compliance with the non-invasive elements of EGDT for sepsis in cancer patients in the emergency center setting was associated with a decreased 28-day in-hospital mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
1
11
0
2
Order By: Relevance
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlesupporting
confidence: 58%
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlesupporting
confidence: 58%
“…Of the 81 potentially relevant publications identified, 33 met our inclusion criteria (Figure 3 ) [ 36 - 68 ]. In total, 17 of these described the physiological changes occurring following FBT [ 36 , 39 , 40 , 45 , 46 , 48 , 50 , 53 - 55 , 57 , 59 , 60 , 62 , 63 , 65 , 66 ] and seven studies described patient-orientated outcome measures [ 37 , 42 , 43 , 49 , 58 , 59 , 64 ].
Figure 3 Study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…In the five studies describing finite volumes of resuscitation fluid, the median volume administered was 2,200 ml (range 1,000 to 5,060 ml) [ 38 , 47 , 51 , 53 , 58 ]. The five remaining studies reported weight-dependent volumes of between 20 and 30 ml/kg of resuscitation (Table 2 ) [ 41 , 43 , 49 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Falhas na identificação de alterações nos parâmetros fisiológicos têm sido associadas a desfechos clínicos desfavoráveis, tais como retorno do paciente à unidade de emergência, tempo prolongado de permanência na instituição, transferência não planejada à unidade de cuidados intensivos e aumento das taxas de mortalidade (BRISTOW et al, 2000;SCHULL;MICHAEL et al, 2011;HANZELKA et al, 2013;CALDER et al, 2014;HOSKING et al, 2014;ANDERSEN et al, 2016).…”
Section: O Papel Da Equipe De Enfermagem No Reconhecimento De Alteraçunclassified